National urban land-use/cover change since the beginning of the 21st century and its policy implications in China. (September 2020) - Kuang, Wenhui
Highlights: National urban land grew from 4.26 × 10 4 km² in 2000 to 6.90 × 10 4 km² in 2015 with a total area of 2.64 × 10 4 km². ISA density dynamic showed a low-density sprawl in 2000-2010 and then filling expansion in 2010–2015. State regional developed strategies play a critically role in spatial divergences on urban expansion.. Abstract: China has experienced rapid urban expansion since the beginning of the 21 st century. Although many previous studies have explored the forces driving urbanization, how policies drive these changes at the national scale has not been fully examined. This research aims to delineate the regional differentiations of urban expansion and related impervious surface area (ISA) density and reveal the socioeconomic and macropolicy factors causing these changes. The result shows that national urban land expanded from 4.26 × 10 4 km² in 2000 to 6.90 × 10 4 km² in 2015 at an unprecedented rate, with an average increasing rate of 1760 km²/yr since 2000. The spatial metrics of ISA density diverted from a low-density sprawl mode during 2000–2010 to a dense expansion mode during 2010–2015, with the highest ISA density of 70.70% in 2015. Regionally, the rate of urban expansion and ISA growth reduced in the coastal zone in 2010–2015. In contrast, urban expansion accelerated in the western and central zones, due to the China Western Development Plan and the Rise of Central China Plan initiated in 1999 and 2006, respectively. Although the concept of "Sponge city" (an urban water management system) was proposed in 2013, the national ISA density still increased due to urban infilling. The overarching issue that must be seriously considered is the tradeoff between the magnitude of urban expansion and ISA density and building sustainable and livable cities in an era of urban transformation.